Effect of dichloroacetate on Lewis lung carcinoma growth and metastasis - Kolesnik, D.L.; Pyaskovskaya, O.N.; Boychuk, I.V.; Dasyukevich, O.I.; Melnikov, O.R.; Tarasov, A.S.; Solyanik, G.I. (Experimental Oncology, 2015)
A hallmark of malignancy is excessive tumor glycolysis, even in the presence of oxygen, which causes lactacidosis in the tumor microenvironment and favors tumor cell proliferation and survival. For this reason antimetabolic agents which target tumor cell metabolism are being researched extensively as promising anticancer drugs. Aim: To study the effect of lactacidosis on survival of Lewis lung carcinoma (LLC) cells at the conditions of nutritional substrate deficiency in vitro and evaluate antitumor and antimetastatic activity against LLC/R9 in vivo. Materials and Methods: LLC variant LLC/R9 was used as experimental tumor model. Tumor cell viability was determined using trypan blue staining. Apoptosis level was counted with the use of Hoechst 33258 dye. Lactate content in the tumor tissue was evaluated by enzyme method with the use of lactate dehydrogenase. Reactive oxygen species was determined using 2.7-dichlorofluorescein diacetate. Effects of dichloroacetate (DCA) on the growth and metastasis of LLC/R9 were analyzed by routine procedures. Evaluation of DCA effect toward electron-transport chain (ETC) components was performed using EPR. Results: It has been shown that at the conditions of lactacidosis and glucose deficiency, LLC/R9 cell viability in vitro was higher by 30% (р < 0.05) and apoptosis level was triply lower (р < 0.05) than these indices at the conditions of glucose deficiency only. In mice with transplanted LLC/R9 tumors treated for 3 weeks per os with DCA at the total dose of 1.5 g/kg of body weight starting from the next day after tumor transplantation, the primary tumor volume was just by 30% lower than that in control group. At the same time, the number and volume of lung metastases in animals treated with DCA were by 59% (р < 0.05) and 94% (р < 0.05) lower, respectively, than these indices in the control group. DCA treatment resulted in nearly 30% increase (р < 0.05) of lactate content in tumor tissue compared to that in the control, but did not affect significantly the levels of heme iron complexes with NO (at gmed = 2.007) in mitochondrial ETC proteins and Fe-S cluster proteins (at g = 1.94) in tumor cells. Conclusions: It has been shown that lactacidosis significantly promoted LLC/R9 cell survival at the conditions of glucose deficiency in vitro. If LLC/R9 developed in vivo, DCA as the compound with antilactacidosis activity did not suppress significantly the primary tumor growth but exerted significant antimetastatic activity. Key Words: dichloroacetate, Lewis lung carcinoma, lactacidosis.